Evaluation of Tumor necrosis factor (TNF-α) Concentration and Renal Function in the Sera of Patients with Type 2 Diabetes in Erbil City - Abdulrazaaq, Zina Abdulmunem (Universitas Muhammadiyah Sidoarjo, 2024)
The research included a total of 70 samples, including 40 samples from patients diagnosed with type 2 diabetes and 30 samples from the control group. The participants' age ranged from 40 to 60 years. The samples were gathered during a one-year duration from the Chronic Diseases Unit / Diabetes Department in the city of Erbil. Later, blood samples were collected from both ill and healthy individuals, and then separated via the process of centrifugation. The variables that were evaluated include glucose, ferritin, Tumor necrosis factor-alpha (TNFα), CRP, urea, creatinine, and uric acid. The results of this research showed a significant rise in the concentrations of glucose, ferritin, TNF-alpha, CRP, urea, creatinine, and uric acid in persons with type II diabetes as compared to the control group.